THE DESCRIPTIVE ANALYSIS OF STUDENTS’ READING COMPREHENSION LEVEL IN PPA IO-0130 OMASIO IN TOURISM TEXT - TELAUMBANUA, NOVTRI YANTI; HAREFA, AFORE TAHIR; WARUWU, YAREDI; MARU’AO, NURSAYANI (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2024)
This study focuses on a descriptive analysis of the level of reading comprehension of PPA IO-0130 Omasio students in understanding tourism texts. This study aims to explore students' abilities in understanding various aspects of tourism texts, including literal, inferential, and critical comprehension. A qualitative descriptive approach was used to collect and analyze data from essay tests and interviews involving 16 student respondents. The findings of the study revealed that the majority of students (87.5%) showed a very good level of literal comprehension, where they were able to identify and recall factual information stated explicitly in the text. In addition, 93.75% of students showed a very good level of inferential comprehension, reflecting their ability to infer and understand implicit meanings in the text. At the critical comprehension level, 93.75% of students achieved a very good score, indicating their ability to evaluate and analyze information in depth, including distinguishing between true and false information and identifying moral messages implied in the text. This study also identified several factors that affect students' reading comprehension, including limited vocabulary, inadequate mastery of grammar, and low reading interest. Many students report difficulty understanding the complex sentence structures and unfamiliar vocabulary often found in formal tourism texts. Lack of interest in reading further exacerbates these challenges, especially when students are not exposed to texts that are relevant or interesting to their daily lives or academic interests. ABSTRAKPenelitian ini berfokus pada analisis deskriptif tingkat pemahaman membaca siswa PPA IO-0130 Omasio dalam memahami teks pariwisata. Penelitian ini bertujuan untuk mengeksplorasi kemampuan siswa dalam memahami berbagai aspek teks pariwisata, termasuk pemahaman literal, inferensial, dan kritis. Pendekatan deskriptif kualitatif digunakan untuk mengumpulkan dan menganalisis data dari tes esai dan wawancara yang melibatkan 16 responden siswa. Temuan penelitian mengungkapkan bahwa mayoritas siswa (87,5%) menunjukkan tingkat pemahaman literal yang sangat baik, di mana mereka dapat mengidentifikasi dan mengingat informasi faktual yang dinyatakan secara eksplisit dalam teks. Selain itu, 93,75% siswa menunjukkan tingkat pemahaman inferensial yang sangat baik, mencerminkan kemampuan mereka untuk menyimpulkan dan memahami makna implisit dalam teks. Pada tingkat pemahaman kritis, 93,75% siswa mencapai skor sangat baik, menunjukkan kemampuan mereka untuk mengevaluasi dan menganalisis informasi secara mendalam, termasuk membedakan antara informasi benar dan salah serta mengidentifikasi pesan moral yang tersirat dalam teks. Penelitian ini juga mengidentifikasi beberapa faktor yang mempengaruhi pemahaman membaca siswa, termasuk keterbatasan kosakata, penguasaan tata bahasa yang kurang memadai, dan minat baca yang rendah. Banyak siswa melaporkan kesulitan dalam memahami struktur kalimat yang kompleks dan kosakata yang tidak familiar yang sering ditemukan dalam teks pariwisata formal. Kurangnya minat baca lebih lanjut memperburuk tantangan-tantangan ini, terutama ketika siswa tidak terpapar pada teks yang relevan atau menarik bagi kehidupan sehari-hari atau minat akademis mereka.